RAILROADS IN THE CENTRAL ASIAN COUNTRIES: ROBLEMS AND PROSPECTS - AZOVSKIY, Igor (CENTRAL ASIA AND THE CAUCASUS, 2004)
The young states of Central Asia inherited a working and generally quite developed railroad net-work from the disintegrated Soviet Union. At the end of 1990, it consisted of 20,890 km of operational lines.1 And although the railroad density was not very high, in Uzbekistan and Kazakhstan it was higher than the same index for Russia (7.8 and 5.3 km per 1,000 sq. km, respectively, and 5.1 in Russia).2What is more, railroad transportation was relatively well equipped. For example, as early as 1931,diesel locomotives were regularly used on certain sections of the Central Asian railroad (for the first time in world practice), and in 1974, this route (the first in the Soviet Union) shifted over completely to diesel locomotive traction. In 1971, electrification began on the Tashkent mainline. By the beginning of the 1990s,the Alma-Ata railroad was characterized by the following indices: 2,967 km (with a total operational length of 4,595 km) were equipped with an automated block system and more than 900 km were semi-automat-ed, diesel locomotives were used along almost the entire length, 749 km were electrified, and non-welded lines on reinforced concrete sleepers were installed on 1,044 km. Locomotive and carriage repair enterprises operated in the region. The formation of the independent states in Central Asia turned a new page in the development of the region’s railroads. Of course, the railroad network in each of these countries has its own special features and specific characteristics, but due to their common historical past, similar economic development, and close economic ties in recent decades relating to railroad functioning and development, today they are faced with resolving several problems that are not only very similar, but also identical for the entire region. The first years of independence in the former Soviet republics were accompanied by such negative phenomena in their economic life as a breakdown in inter-economic ties, rise in inflation, drop in production, financial-credit instability, and deterioration in the population’s standard of living. For example, in 1991-1994 in Kazakhstan, the GDP fell by 43% and in Tajikistan by 49%; during the same time industrial production in Kazakhstan dropped by 48%, and investments by 71%.3 This could not help but affect the operation of the railroads, where the volume of freight shipments was on the constant decline. In 1995 (compared with 1991) this volume dropped by almost half in Kazakhstan and Uzbekistan, three-fold in Turkmenistan, and seven-fold in Kyrgyzstan and Tajikistan. And only during the second half of the 1990s was some improvement noted. But in most of the countries these results still lag far behind the indices of the Soviet period. As for passenger traffic, the drop in the standard of living, as well as the political instability have led to a severe decline in the population’s mobility. The indices have decreased, although not as dramatically as in freight shipments. Nor is a clear-cut temporal trend observed. This shows that the decrease in passenger traffic is primarily for internal and not regional reasons. For example, as a result of the 25% in-crease in the cost of rail tickets in Tajikistan in 1998, the number of passengers traveling by rail dropped by almost half in 1999.